Ban the Cellphone Ban - Horn, Michael B (Education next, 2023)
According to the federal education department, more than three quarters of public schools prohibited the non-academic use of cellphones during school hours in 2019–20. According to the Centers for Disease Control, in 2021 44 percent of U.S. high-school students reported “persistent feelings of sadness or hopelessness” in the past year—up from 26 percent in 2009. With the active learning methodologies at the heart of these apps, the learning opportunities on mobile devices are in many ways superior to many of the more passive, video- and text-based ones built for laptops and personal computers. (Even before smartphones, a version of this called “language lab” put individual students at headphone stations to work independently with the education technology of the day before rejoining group conversations.) The phone is central to the design of the learning experience.